Easing wheelchair control by gaze-based estimation of intended motion - Bartolein, Christian; Wagner, Achim; Jipp, Meike; Badreddin, Essameddin (IFAC Proceedings Volumes, 2008)
An assistive system easing wheelchair control for severely disabled users is presented. To compensate for the restricted information that can be provided using speciality controls, the person's gaze is used to estimate the intended motion direction. The novelty of the presented method is that motion-relevant portions of natural gaze behavior can be distinguished from non-relevant. Producing wheelchair movement only from relevant gaze information leads to an increased acceptance of powered wheelchairs in the user group and to improved safety.
Gesehen am 14.06.2019